10.73: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
 
Line 14: Line 14:
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|-  
|-  
| [https://dlmf.nist.gov/10.73.E1 10.73.E1] || [[Item:Q3912|<math>\frac{1}{r}\pderiv{}{r}\left(r\pderiv{V}{r}\right)+\frac{1}{r^{2}}\pderiv[2]{V}{\phi}+\pderiv[2]{V}{z} = 0</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{1}{r}\pderiv{}{r}\left(r\pderiv{V}{r}\right)+\frac{1}{r^{2}}\pderiv[2]{V}{\phi}+\pderiv[2]{V}{z} = 0</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>(1)/(r)*diff((r*diff(V, r))+(1)/((r)^(2))*diff(V, [phi$(2)]), r)+ diff(V, [z$(2)]) = 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[1,r]*D[(r*D[V, r])+Divide[1,(r)^(2)]*D[V, {\[Phi], 2}], r]+ D[V, {z, 2}] == 0</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 300]
| [https://dlmf.nist.gov/10.73.E1 10.73.E1] || <math qid="Q3912">\frac{1}{r}\pderiv{}{r}\left(r\pderiv{V}{r}\right)+\frac{1}{r^{2}}\pderiv[2]{V}{\phi}+\pderiv[2]{V}{z} = 0</math><br><syntaxhighlight lang="tex" style="font-size: 75%;" inline>\frac{1}{r}\pderiv{}{r}\left(r\pderiv{V}{r}\right)+\frac{1}{r^{2}}\pderiv[2]{V}{\phi}+\pderiv[2]{V}{z} = 0</syntaxhighlight> || <math></math> || <syntaxhighlight lang=mathematica>(1)/(r)*diff((r*diff(V, r))+(1)/((r)^(2))*diff(V, [phi$(2)]), r)+ diff(V, [z$(2)]) = 0</syntaxhighlight> || <syntaxhighlight lang=mathematica>Divide[1,r]*D[(r*D[V, r])+Divide[1,(r)^(2)]*D[V, {\[Phi], 2}], r]+ D[V, {z, 2}] == 0</syntaxhighlight> || Successful || Successful || - || Successful [Tested: 300]
|}
|}
</div>
</div>

Latest revision as of 11:28, 28 June 2021


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
10.73.E1 1 r r ( r V r ) + 1 r 2 2 V ϕ 2 + 2 V z 2 = 0 1 𝑟 partial-derivative 𝑟 𝑟 partial-derivative 𝑉 𝑟 1 superscript 𝑟 2 partial-derivative 𝑉 italic-ϕ 2 partial-derivative 𝑉 𝑧 2 0 {\displaystyle{\displaystyle\frac{1}{r}\frac{\partial}{\partial r}\left(r\frac% {\partial V}{\partial r}\right)+\frac{1}{r^{2}}\frac{{\partial}^{2}V}{{% \partial\phi}^{2}}+\frac{{\partial}^{2}V}{{\partial z}^{2}}=0}}
\frac{1}{r}\pderiv{}{r}\left(r\pderiv{V}{r}\right)+\frac{1}{r^{2}}\pderiv[2]{V}{\phi}+\pderiv[2]{V}{z} = 0

(1)/(r)*diff((r*diff(V, r))+(1)/((r)^(2))*diff(V, [phi$(2)]), r)+ diff(V, [z$(2)]) = 0
Divide[1,r]*D[(r*D[V, r])+Divide[1,(r)^(2)]*D[V, {\[Phi], 2}], r]+ D[V, {z, 2}] == 0
Successful Successful - Successful [Tested: 300]